Tradisi Gaukang Karaeng Galesong di Desa Galesong Kabupaten Takalar - Muh Ashar Arsad; Firdaus W. Suhaeb (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to determine the origin of the existence of Gaukang Karaeng Galesong in Galesong Village, Takalar Regency and the Symbolic Meaning of the implementation of the Gaukang Karaeng Galesong Tradition in Galesong Village, Takalar Regency. The type of this research is descriptive qualitative research, where in selecting informants purposive sampling technique is used with various criteria determined, namely the Management of the Galesong Traditional Institute, the Karaeng Galesong Family, and the Gaukang Tradition Actors. Data collection techniques used are observation, interviews and documentation. Data reduction, data presentation, and drawing conclusions are ways to analyze data. The results of this study indicate that: (1) The beginning of the existence of Gaukang Karaeng Galesong was started from a supernatural event experienced by a Papekang when he was about to go to sea until the process of being found by Boe Janggo with Daengta Lowa-Lowa and the Papekang. (2) The symbolic meaning of the implementation of the Gaukang Karaeng Galesong Tradition is to analyze the meanings behind each series of the implementation of the Gaukang Karaeng Galesong Tradition including (a) Appabballe which means Treating Memories of the coming of Gaukang, (b) Pappasabbi which means appreciation and respect for Gaukang, (c) Appalili means avoiding danger (d) Appadongko Raki'-Raki' is interpreted as a form of offering to ancestors, (e) Akrate' Juma' is interpreted as a form of servitude for the Galesong community to God Almighty.